THE INTERMEDIATE RAIL FASTENING CAT-5 IN KAZAKHSTAN - Fink, V. K.; Kosenko, S. A. (Science and Transport Progress, 2008)
In the article the issues of testing the parts of a fastening КПП-5 on reliability are considered and the modem way of fixing the backing anchor in a form at a factory of ferro-concrete sleepers is presented.